Drug-Induced Anaphylaxis: An Update on Epidemiology and Risk Factors - Regateiro, FS (2020)
Drug hypersensitivity is one of the most frequent causes of anaphylaxis, particularly in adults and in hospitalized patients. Drug-induced anaphylaxis (DIA) is also associated with more severe outcomes than other anaphylaxis triggers, and drugs are responsible for the majority of deaths due to anaphylaxis. We here review the current knowledge on the incidence, prevalence, drugs involved, mortality, and mortality risk factors for DIA. The incidence of both anaphylaxis and DIA seems to be increasing worldwide. Antibiotics and analgesics are the most frequently reported triggers of DIA. However, the importance of other drug groups should be taken into account, especially in particular settings (e.g., peri-operative and oncology). The identification of risk factors, geographical variables, and drugs associated with higher risk for DIA may improve the outcomes of this entity.